Fast, Robust, and Laser-Free Universal Entangling Gates for Trapped-Ion Quantum Computing - Markus Nünnerich; Daniel Cohen; Patrick Barthel; Patrick H. Huber; Dorna Niroomand; Alex Retzker; Christof Wunderlich (Physical Review X)
A novel two-qubit entangling gate for trapped-ion quantum processors is proposed theoretically and demonstrated experimentally. During the gate, double-dressed quantum states are created by applying a phase-modulated continuous driving field. The speed of this quantum gate is an order of magnitude higher than that of previously demonstrated rf controlled two-qubit entangling gates in static magnetic field gradients. At the same time, the field driving the gate dynamically decouples the qubits from amplitude and frequency noise, increasing the qubits’ coherence time by 3 orders of magnitude. The gate requires only a single continuous rf field per qubit, making it well suited for scaling a quantum processor to large numbers of qubits. Implementing this entangling gate, we generate the Bell states |Φ^{+}⟩ and |Ψ^{+}⟩ in less than or equal to 313  μs with fidelities up to 98_{-3}^{+2}% in a static magnetic gradient of only 19.09  T/m. At higher magnetic field gradients, the entangling gate speed can be further improved to match that of laser-based counterparts.